Factors Influencing Entrepreneurship : A Study on MSMEs Under Industrial Infrastructure - Das, Daisy; Das, Tilak Chandra (AMC Indian Journal of Entrepreneurship, 2021)
Micro, small, and medium enterprises play an important role for developing economies like India. Industrial infrastructure is essential for growth of industries. An attempt was made to examine the role of Assam Industrial Infrastructure Development Corporation in promotion of entrepreneurship under industrial infrastructure. Industrial infrastructure includes industrial estate, industrial area, mini industrial estate, integrated infrastructure development center, industrial growth center etc. in the state. A research enquiry was done for 177 micro, small, and medium enterprises located in the Industrial Infrastructure situated in Kamrup (metro) and Kamrul (rural) district of Assam. It was found that entrepreneurs are influenced by ambition factors, compelling factors, and facilitating factors.